The effect of hyperlipidemia on hearing function - Karlidag, Turgut; Açik, Yasemin; Kaygusuz, Irfan; Yalçin, Sinasi; Güngör, M Yüksel; Demirbag, Erhan (My University, 2002)
OBJECTIVES: We evaluated the effects of hyperlipidemia on hearing function. PATIENTS AND METHODS: The study included 274 hyperlipidemic patients (176 females, 98 males; age range 35 to 60 years) who manifested normal tympanic membrane findings, no history of noise exposure, and chronic systemic or ear diseases. Sixty healthy subjects (36 females, 24 males) with normal serum lipid levels were enrolled as controls. Subjects who had elevated serum total cholesterol, triglyceride, and very low density lipoprotein (VLDL) levels, and normal lipid levels were divided into four groups and their hearing functions were analysed with pure-tone audiometry. RESULTS: Evaluation of all groups showed significantly increased hearing levels at three frequencies in female patients, and at six frequencies in male patients (p < 0.05). Significant increases in hearing levels were observed both in females and males at 8000 Hz in three groups, at 6000 Hz in the VLDL group, and in males at 2000 Hz in the total cholesterol and VLDL groups (p < 0.05). When both female and male patients were evaluated together, the largest difference was detected in the VLDL group at five frequencies. CONCLUSION: The findings of our study suggest that hyperlipidemia may have a role on the occurrence of sensorineural hearing loss.
Hiperlipideminin işitme fonksiyonu üzerine etkisi.
Keywords: Adult; Audiometry, Pure-Tone; Case-Control Studies; Cholesterol; Cholesterol, LDL; Female; Hearing; Hearing Loss, Sensorineural; Humans; Hyperlipidemias; Lipids; Male; Middle Aged; Triglycerides; cholesterol; lipid; low density lipoprotein cholesterol; triacylglycerol; adult; article; blood; case control study; female; hearing; human; hyperlipidemia; male; middle aged; perception deafness; physiology; pure tone audiometry